Interleukin-6 is increased in plasma and cerebrospinal fluid of community-dwelling domestic dogs with acute ischaemic stroke. Issue 3 (8th February 2017) - Gredal, Hanne; Thomsen, Barbara B.; Boza-Serrano, Antonio; Garosi, Laurent; Rusbridge, Clare; Anthony, Daniel; Møller, Arne; Finsen, Bente; Deierborg, Tomas; Lambertsen, Kate L.; Berendt, Mette
Abstract : Inflammatory cytokines are potential modulators of infarct progression in acute ischaemic stroke, and are therefore possible targets for future treatment strategies. Cytokine studies in animal models of surgically induced stroke may, however, be influenced by the fact that the surgical intervention itself contributes towards the cytokine response. Community-dwelling domestic dogs suffer from spontaneous ischaemic stroke, and therefore, offer the opportunity to study the cytokine response in a noninvasive set-up. The aims of this study were to investigate cytokine concentrations in plasma and cerebrospinal fluid (CSF) in dogs with acute ischaemic stroke and to search for correlations between infarct volume and cytokine concentrations. Blood and CSF were collected from dogs less than 72 h after a spontaneous ischaemic stroke. Infarct volumes were estimated on MRIs. Interleukin (IL)-2, IL-6, IL-8, IL-10 and tumour necrosis factor in the plasma, CSF and brain homogenates were measured using a canine-specific multiplex immunoassay. IL-6 was significantly increased in plasma ( P =0.04) and CSF ( P =0.04) in stroke dogs compared with healthy controls. The concentrations of other cytokines, such as tumour necrosis factor and IL-2, were unchanged. Plasma IL-8 levels correlated significantly with infarct volume (Spearman's r =0.8, P =0.013). The findings showed increased concentrations of IL-6 in the plasma and CSF of dogs with acute ischaemic stroke comparable to humans. We believe that dogs with spontaneous stroke offer a unique, noninvasive means of studying the inflammatory processes that accompany stroke while reducing confounds that are unavoidable in experimental models.